2007
DOI: 10.1177/1043454206296018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distraction on Pain, Fear, and Distress During Venous Port Access and Venipuncture in Children and Adolescents With Cancer

Abstract: This study evaluates the effect of self-selected distracters (ie, bubbles, I Spy: Super Challenger book, music table, virtual reality glasses, or handheld video games) on pain, fear, and distress in 50 children and adolescents with cancer, ages 5 to 18, with port access or venipuncture. Using an intervention-comparison group design, participants were randomized to the comparison group (n = 28) to receive standard care or intervention group (n = 22) to receive distraction plus standard care. All participants ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
172
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(194 citation statements)
references
References 50 publications
13
172
1
5
Order By: Relevance
“…only the study by WindichBiermeier et al approached these three items, using both active (soap bubbles, game Boy®, interactive books) and passive (audio- books, Virtual reality glasses) distracters. these authors stated that distraction itself is efficient in reducing pain, but they weren't able to rate single distracters' efficacy 28 . our data show that there is no difference in self-reported pain when adding a videogame distraction technique to eMlA cream.…”
Section: Discussionmentioning
confidence: 99%
“…only the study by WindichBiermeier et al approached these three items, using both active (soap bubbles, game Boy®, interactive books) and passive (audio- books, Virtual reality glasses) distracters. these authors stated that distraction itself is efficient in reducing pain, but they weren't able to rate single distracters' efficacy 28 . our data show that there is no difference in self-reported pain when adding a videogame distraction technique to eMlA cream.…”
Section: Discussionmentioning
confidence: 99%
“…Involving the family during care is critical. Studies have shown that parents are able to play an active role in supporting and training their children during the procedure 13 , fact that is confirmed by other studies which have also counted on parents' role during intervention and/or during evaluation 12,[14][15][16][17][18][19]21 . The study working with party blower 18,19 , has also effectively incorporated parents in the intervention process, even evaluating their distress during procedure 19 .…”
Section: Kuttner Bowman and Teasdale 21mentioning
confidence: 53%
“…One should also consider that some studies have reported that topic local anesthetics would be used at puncture site, which could interfere with results 12,13,15 . Still about virtual reality, it is inferred from the literature the need for further studies about the application of this technology taking into consideration its cost-effectiveness ratio 15 .…”
Section: Kuttner Bowman and Teasdale 21mentioning
confidence: 99%
“… The majority of the research efforts have focused on clinic-based applications running on PC-based platforms [18][19][20][21][22][23][24][25][26][27][28][29][30], with only a limited number of studies paying attention to the need for mobile pain assessment. In fact, it is surprising that very few (if any) have been 6 built and ported to mobile platforms.…”
Section: Discussionmentioning
confidence: 99%